Sustainable Air Conditioning Systems - Ghenai, Chaouki; Salameh, Tareq (IntechOpen, 2018)
Air conditioning system is one of the major consumers of electrical energy in many parts of the world today. It represents between 40 and 70% of the energy consumption in commercial buildings. The demand of energy for air conditioning systems is expected to increase further in the next decades due to the population growth, the new economic boom, and the urbanization development. The rapid growth of air conditioning and electricity consumption will contribute further to climate change if fossil and nonrenewable resources are used. More energy-efficient and renewable energy-based air conditioning systems to accomplish space cooling are needed. This book intends to provide the reader with a comprehensive overview of the current state of the art in sustainable air conditioning technologies and focus on the most recent research and development on green air conditioning systems including energy-efficient and renewable energy-based air conditioning systems.